PERANCANGAN DASHBOARD VISUALISASI GUDANG BAHAN PENGEMAS MELALUI PENDEKATAN METODE DEDICATED STORAGE PT. XYZ - Siti Fadilah Kurnia Praja (2023)
PT. XYZ is one of the largest manufacturing companies in the cosmetics sector and a pioneer of halal cosmetics manufacturers in Indonesia. Some of the leading brands of PT. XYZ includes W, MO, Em, Ka, and others. Previously, this company had never evaluated the layout of suppliers who had implemented a pull system. Therefore, it is necessary to evaluate the warehouse layout to determine the efficiency of the actual layout using the Dedicated Storage Method. Measurement is carried out in several stages, namely by identifying the amount of entry and exit of data on receipt, maximum stock, and delivery, the amount of space requirements (Space Requirement) and Throughput, and validating the model using machine learning K-Nearest Neighbor (K-NN) to obtain a more efficient proposal layout. According to the results of the study, calculations using the dedicated storage method resulted in a total travel distance of actual conditions of 7153.06 m/week and a proposal of 3290.13 m/week with a percentage decrease of 271.41%. With a comparison of the two layouts, the proposed layout has a greater decrease in total travel distance compared to the actual layout. Therefore, it can be said that the proposed layout is more efficient. Also, the calculation of model evaluation using K-NN was 0.42105 or 42.11%.